ENHANCING STUDENTS’ DESCRIPTIVE WRITING ABILITY THROUGH THE PICTURE WORD INDUCTIVE MODEL (PWIM) IN GRADE X AT SMAN 1 SUKOMORO NGANJUK - Putri Nurjannah; Triana Wuri Cahyanti (Journal of English Language Education, 2026)
Background: This study aims to evaluate the effectiveness of the Picture Word Inductive Model (PWIM) in enhancing the descriptive writing skills of tenth-grade students at SMAN 1 Sukomoro. The research design employed was pre-experimental with a one-group pretest-posttest model. A total of 36 students from class X-5 participated as research subjects. Data were collected through written tests administered before and after the treatment and analyzed using the paired sample t-test. The results revealed a significant improvement in students' writing skills after the implementation of PWIM. The average score increased from 52.56 (pre-test) to 70.42 (post-test), with a significance value of p = 0.000 (< 0.05), leading to the rejection of the Null Hypothesis (H₀) and the acceptance of the Alternative Hypothesis (Ha). These findings indicate that PWIM is an effective strategy for teaching writing, particularly in the development of descriptive texts. This study provides important implications for teachers in selecting more innovative, contextual, and participatory approaches to writing instruction. Based on these findings, it is recommended that PWIM be implemented as an effective and innovative writing instruction strategy in secondary-level English classes to enhance students’ descriptive writing skills.